The Impact of Portal Vein Thrombosis on the Prognosis of Patients With Cirrhosis: A Retrospective Propensity-Score Matched Study - Chen, Zhiji; Ran, Tao; Cao, Haiyan; Xu, Feng; Zhou, Zhi-hang; He, Song (Frontiers in Medicine, 2021)
OBJECTIVES: To investigate the impact of portal vein thrombosis (PVT) on cirrhosis decompensation and survival of cirrhosis. METHODS: In this retrospective observational study between January 2012 and August 2020, 117 patients with cirrhotic PVT and 125 patients with cirrhosis were included. Propensity score matching (PSM) was applied to reduce the bias. The clinical characteristics of non-tumoral PVT in cirrhosis and its influence on cirrhosis decompensation and survival were analyzed. Results: The median follow-up for the PVT group was 15 (8.0-23.0) months and for the non-thrombosis group 14 (8.0-23.5) months. The presence of PVT was related with esophageal varices, higher Child-Pugh score and MELD score (P＜0.05). Most PVTs were partial (106/117). Nonocclusive PVT disappeared on later examinations in 32/106 patients (30.19%), of which 6 patients reappeared. All the 11 patients with occlusive PVT remained occlusive, among which 5 patients (45.45%) developed portal cavernoma. There was no significant correlation between PVT and decompensation or survival before or after PSM. Multivariate analysis identified only Child-Pugh score (HR=2.210, 95%CI: 1.332-3.667) and serum sodium level (HR=0.818, 95%CI: 0.717-0.933) as independent factors for death. Conclusion: Though PVT is associated with greater Child-Pugh score and MELD score, it has no significant impact on the progression of cirrhosis.